C++ how to program introducing the new C++14 standard. - Deitel, Paul J.; Deitel, Harvey M., 1945- (Pearson Education Limited, 2017)
For courses in C++ Programming The best-selling C++ How to Program is accessible to readers with little or no programming experience, yet comprehensive enough for the professional programmer. The Deitels' signature live-code approach presents the concepts in the context of full working programs followed by sample executions. The early objects approach gets readers thinking about objects immediately-allowing them to more thoroughly master the concepts. Emphasis is placed on achieving program clarity and building well-engineered software. Interesting, entertaining, and challenging exercises enco.